Uso do solo e desmatamento nas regiões da Amazônia Legal Brasileira: condicionantes econômicos e impactos de políticas públicas - Terciane Sabadini Carvalho (2014)
The deforestation in the Legal Brazilian Amazon has attracted the attention of researchers and government around measures and policies that involve both its measurement and control. Besides maintaining a high level of biodiversity, the Amazon forest has also been discussion agenda of the international community, especially on the growing debate about the causes and consequences of global climate change. Brazil has confirmed voluntary national targets for reducing emissions of greenhouse gases (GHG) that includes an 80% reduction in Amazon deforestation by 2020. The limited supply of land restricts the expansion of the agricultural frontier, which is one of the most important economic activities in the region. Thus, it seems relevant to investigate aspects of a possible trade-off between the goals of environmental conservation (reducing deforestation) and economic growth in the region. The main goal of this thesis is to project the economic losses resulting from a policy to control deforestation in the Amazon. In methodological terms, this thesis advances in developing a Dynamic Interregional Computable General Equilibrium Model for 30 regions in Amazon, and include an ILUC model (indirect land use change) that allows conversion of land in different uses. With the model, it is also projected an economic growth scenario of the Amazon regions between 2006 and 2030, a policy of forest concession and the issue of agriculture technical improvement in the region is investigated. The results showed that the regions that present a higher GDP growth would be those that are on the deforestation frontier, mainly the producing regions of soybean and cattle. The most affected regions with the policy to control deforestation are the major producing regions of soybean and cattle and the regions dominated by family farms. The three regions that receive forest concessions would have positive impacts on economic indicators. However, not enough to nullify or override the negative impacts of the policy of deforestation control. The annual productivity gain of land required is approximately 1.4%, so that the policy of control will not generate economic losses in the Amazon.